Vertical Integration and Foreclosure: Evidence from Production Network Data - Boehm, Johannes; Sonntag, Jan (Management Science, 2023)
This paper studies the prevalence of potential anticompetitive effects of vertical mergers using a novel data set on U.S. and international buyer-seller relationships and across a large range of industries. We find that relationships are more likely to break when suppliers vertically integrate with one of the buyers’ competitors than when they vertically integrate with an unrelated firm. This relationship holds for both domestic and cross-border mergers and for domestic and international relationships. It also holds when instrumenting mergers using exogenous downward pressure on the supplier’s stock prices, suggesting that reverse causality is unlikely to explain the result. In contrast, the relationship vanishes when using rumored or announced but not completed integration events. Firms experience a substantial drop in sales when one of their suppliers integrates with one of their competitors. This sales drop is mitigated if the firm has alternative suppliers in place. These findings are consistent with anticompetitive effects of vertical mergers, such as vertical foreclosure, rising input costs for rivals, or self-foreclosure. This paper was accepted by Joshua Gans, business strategy. Funding: This work was supported by a Banque de France/Sciences Po Partnership. Supplemental Material: The data files and online appendices are available at https://doi.org/10.1287/mnsc.2022.4363 .